Effects of a neuromuscular warm-up program in youth female soccer players - Isla, E.; Romero-Moraleda, B.; Moya, J. M.; Esparza-Ros, F.; Mallo, J. (Journal of Human Kinetics, 2021)
The protective effects of different warm-up injury prevention routines in youth female soccer players have been demonstrated in the literature, however, there is a paucity of information regarding the effects that these kinds of programs have on soccer-specific physical performance variables. The purpose of this study was to assess the effectiveness of a 12-week neuromuscular warm-up program on physical performance in youth female soccer players. Players (age: 13.94 ± 0.82 years) were divided into two groups. One group performed a neuromuscular activation program (n = 21) twice per week whereas the other group (control, n = 17) continued with their habitual warm-up routine for the same duration. Both groups of players performed strength, jumping and balance tests before and after the intervention period. Substantially greater improvements were detected in the mean velocity for the squat (p < 0.001; Effect Size = 0.95) and the hip thrust (p < 0.001; Effect Size = 0.51) in the experimental group in comparison to the control group. In addition, after the intervention period players in the experimental group showed an increase in the jumping height in the unloaded double-leg and single-leg counter-movement jumps (p = 0.003-0.012; Effect Size = 0.42-0.46). The results of this study provide evidence that a 12-week neuromuscular warm-up program can be effective to improve different physical performance variables in youth female soccer players.